The Fiber Profile of Midrib Waste on Salak Sidempuan Fermented with Phanerochaete chrysosporium - Rikardo Silaban (Faculty of Agriculture, Tompotika Luwuk University, 2022)
Feed alternative is become the major concern for livestock industry in order to provide the continuously feeding. Feed technology system based on agriculture wastes were the modified strategy to gain the other sources of feed raw materials. Salak Sidempuan is performed similar with the Palm plantations which is produced the potential midrib waste. Nutritionally, the product will feed the animal to increase the performance. The research aims to evaluate the proximate profile especially the fiber contents of midrib waste of Salak Sidempuan fermented with white root fungi. The fifth experiments were evaluated after the measuring period by using the Phanerochaete chrysosporium and replicated in 4 times. Experiments were P0 (control), P1 (5%inoculant of P. chrysosporium), P2 (10%inoculant of P. chrysosporium), P3 (15%inoculant of P. chrysosporium), and P4 (20%inoculant of P. chrysosporium). A completely randomized design was used to determine the statistical effect on dry matter, organic matter, crude fiber and lignin. Results showed that the addition of inoculant about 20% signifantly effected the increasing on dry matter and organic matter while followed the decreasing of fiber contents. In conclusion, fermentation of midrib waste with Phanerochaete chrysosporium is potentially degradated the fiber content itselves.